Induction of Ampicillin Resistance in E.coli and Salmonella species by Sub-lethal Doses - Rasool, Muhammad Salman; Siddiqui, Fraz; Rasool, Sheikh Ajaz; Hafiz, Saleem (International Journal of Pathology, 2018)
Background: Antibiotic resistance is increasing steadily in pathogenic bacteria all over the world. The inductionof bacterial resistance by sub-lethal concentrations of ampicillin may be due to mutations and adaptability to surviveat sub-minimum inhibitory concentrations of ampicillin.Objective: Demonstrate in-vitro model of acquisition of ampicillin resistance at sub-lethal concentrations.Material and Methods: E.coli and Salmonella species were identified by conventional biochemical reactions, API20 E kits and by anti sera. Antibiotic disc diffusion tests and Minimum inhibitory concentrations were performedaccording to CLSI (2012). 56 clinical isolates of E.coli and 47 strains of Salmonella species were step wise exposed tosub-lethal concentrations of ampicillin.Results: Out of 56 isolates of E.coli, 9 strains developed permanent resistance to ampicillin and 17 adapted to intermediateresistant levels of ampicillin. Out of 47 isolates of Salmonella species, 8 strains developed permanentresistance to ampicillin and 16 got adapted to intermediate resistance concentrations. Few strains showed crossresistance to various antibiotics after exposure to ampicillin. Sub lethal concentrations of ampicillin leads to thedevelopment of resistance which may have therapeutic implications.Conclusion: Sub lethal concentrations of ampicillin should be avoided because exposure to these concentrationsmay create the ability in bacteria to adapt higher concentrations of ampicillin and trigger the bacteria to developthe resistance not only against ampicillin but also other groups of antibiotics.